Home and workplace neighborhood SES and behavior-related health: a within-individual analysis. (30th September 2020) - Raza, A; Hanson, L M; Westerlund, H; Halonen, J
Abstract: Background: Although the influence of individual and home neighborhood socioeconomic status (SES) on health-related behaviors has been widely studied, majority of the evidence is from cross-sectional studies. Moreover, studies on associations of workplace SES with health-related behaviors are almost non-existent. Objective: To investigate associations between home and work neighborhood SES and behavior-related health in gainfully employed individuals. Methods: Participants were from the Swedish Longitudinal Occupational Survey of Health with response to minimum two surveys between 2012 and 2018. We had 13163 individuals with complete data on exposure and covariates with total of 36925 observations. Neighborhood SES was determined as an index using mean income, education attainment, and unemployment rate within a 500 m buffer around home and workplace address. We used fixed effects method with conditional logistic regression to investigate longitudinal within-individual associations for home, workplace and their weighted summary neighborhood SES with self-reported obesity, physical activity, smoking, excessive alcohol consumption, sedentary lifestyle, and sleep problems. We included age, marital status, individuals' occupational position, presence of children, chronic disease, depressive symptoms, and work strain as covariates. Results: The workers were more likely to consume alcohol excessively when their workplace was located in the highest SES area compared to time when their workplace was located in the lowest SES area (adjusted odds ratio 1.98; 95% confidence interval 1.12-3.49). Contrarily, socioeconomic status of home neighborhood was observed to be associated with low alcohol consumption. We observed no associations for other behavior-related health outcomes. Conclusions: These within-individual comparisons suggest that having workplace in a high SES area may be favorable for excessive alcohol consumption. Key messages: Workplace in a high socioeconomic area may be favorable of excessive alcohol consumption, while such association were not observed for home neighborhood. Consideration of work neighborhood SES along with home neighborhood SES and individual variables can enhance our understanding of the influence of environments on health behaviors.